Analisis Perbandingan Kinerja Keuangan Perusahaan Sebelum dan Sesudah Initial Public Offering (IPO) pada Perusahaan yang Listing di BEI - Fitricia, Kevin; Warsitasari, Wahyu Dwi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study was to compare the financial results of IDX companies before and after their IPO to determine if there is a correlation between the two. Purposive sampling was employed to choose a subset of the study population (n=42) from among the full (n=51) population. All information for this study comes directly from the IDX's official website, making it a secondary data source. A company's financial results before and after its initial public offering (IPO) serve as independent and dependent variables, respectively. While a documentation study is utilized to collect data. A comparison of the company's liquidity ratio, leverage ratio, profitability ratio, and activity ratio before and after its IPO was found to be statistically significant (P .05) or not (P >.05), respectively, using the Wilcoxon Signede-rank test method. Keywords: Initial Public Offering (IPO), Liquidity Ratio, Leverage Ratio, Profitability Ratio, and Activity Ratio, Financial Performance.